Flood resilience loci SUBMERGENCE 1 and ANAEROBIC GERMINATION 1 interact in seedlings established underwater - Alam, Rejbana; Hummel, Maureen; Yeung, Elaine; Locke, Anna M.; Ignacio, John Carlos I.; Baltazar, Miriam D.; Jia, Zhenyu; Ismail, Abdelbagi M.; Septiningsih, Endang M.; Bailey-Serres, Julia (Wiley, 2020)
Crops with resilience to multiple climatic stresses are essential for increased yield stability. Here, we evaluate the interaction between two loci associated with flooding survival in rice (Oryza sativa L.). ANAEROBIC GERMINATION 1 (AG1), encoding TREHALOSE 6‐PHOSPHATE PHOSPHATASE 7 (TPP7), promotes mobilization of endosperm reserves to enhance the elongation of a hollow coleoptile in seeds that are seeded directly into shallow paddies. SUBMERGENCE 1 (SUB1), encoding the ethylene‐responsive transcription factor SUB1A‐1, confers tolerance to complete submergence by dampening carbohydrate catabolism, to enhance recovery upon desubmergence. Interactions between AG1/TPP7 and SUB1/SUB1A‐1 were investigated under three flooding scenarios using four near‐isogenic lines by surveying growth and survival. Pyramiding of the two loci does not negatively affect anaerobic germination or vegetative‐stage submergence tolerance. However, the pyramided AG1 SUB1 genotype displays reduced survival when seeds are planted underwater and maintained under submergence for 16 d. To better understand the roles of TPP7 and SUB1A‐1 and their interaction, temporal changes in carbohydrates and shoot transcriptomes were monitored in the four genotypes varying at the two loci at four developmental timeponts, from day 2 after seeding through day 14 of complete submergence. TPP7 enhances early coleoptile elongation, whereas SUB1A‐1 promotes precocious photoautotrophy and then restricts underwater elongation. By contrast, pyramiding of the AG1 and SUB1 slows elongation growth, the transition to photoautotrophy, and survival. mRNA‐sequencing highlights time‐dependent and genotype‐specific regulation of mRNAs associated with DNA repair, cell cycle, chromatin modification, plastid biogenesis, carbohydrate catabolism and transport, elongation growth, and other processes. These results suggest that interactions between AG1/TPP7 and SUB1/SUB1A‐1 could impact seedling establishment if paddy depth is not effectively managed after direct seeding.